A digital maturity model for the education enterprise. (3rd April 2022) - AL-Ali, Maytha; Marks, Adam
ABSTRACT: Digital transformation in higher education, especially after COVID-19, is seen as inevitable. This research explores digital transformation's maturity and challenges within the education enterprise. The significance of this study stems from the critical role digital transformation and higher education play in today's digital economy, and digital learning, especially with the impact of COVID-19. This study proposes a new model to measure digital transformation maturity assessment in the education enterprise, based on Deloitte's 2019 digital transformation assessment model, and Petkovic et al.'s [2014. Cloud Computing Support to University Business Processes in External Collaboration." Acta Polytechnica Hungarica 11 (3): 181–200] mega and major higher education process mapping. The study triangulates the findings of multiple research instruments, including survey, interviews, case study, and direct observation. The research findings show a gap between digital transformation's maturity perception, and core requirements. A stronger focus on enabling processes, and a lack of wholistic vision, digital transformation competency, and data structure were among the leading challenges in digital transformation.